Physico-Chemical Studies of Enamel Cover Industry Wastewater - Ozdemir, Celalettin; Karatas, Mustafa; Sahinkaya, Serkan; Emin Argun, Mehmet (Asian Journal of Chemistry, 2010)
The enamel plating industry wastewater has a reputation for being a major pollutant. Plating has become a major industry and is one of the fastest growing sectors of the world economy. Enamel industry is typically associated with detrimental environmental effects. There was not exactly a study source of enamel cover wastewater and characteristics in Turkey. This study has been made for completing this subject and to solve available problems. To achieve the objectives of the study, the samples taken from metal plating wastewater, were analyzed in the laboratories. Wastewater produced plating unit in enamel have high chemical oxygen demand (394 mg L-1) and suspended solid (486 mg L-1) concentrations. In this study, physico-chemical properties were also evaluated in enamel plating industry wastewater. The optimum polielectrolyte dose with lime addition was determined as 1660 mgL-1 in order to obtain 86 % COD, 94 % TSS removal effiency at pH 9.